Paradox between Religion and Biotechnology in Ishiguro's Never Let Me Go - Dewan, Motikala Subba (Bon Voyage, 2019)
In the modern world, biotechnology plays a vital role to help improve human lives and the health of the planet; and, similarly, we cannot deny the significance of religion that helps to shape the human’s mind and spiritual growth. Both are equally important even though many secularists and nonbelievers tend to regard religion and science (technology) as vitally incompatible. This incompatibility is also imagined to extend the relationship between religion and biotechnology. We cannot envisage the present world without technology, which is often rooted, sometimes unknowingly in religious myths and ancient dreams and it is unfortunate sometimes technology has proven itself capable of causing terrible problems in the name of humanity and one of the reasons for this may be the religious impulses people are ignoring. This research article tries to analyze the paradox between religion and biotechnology based on humanity raised by Kazuo Ishuguro in the novel Never Let Me Go. It tries to examine the scientific credibility and the religious values for humanity in the futuristic world.